Mesenchymal stem cell-derived exosomes and treatment in atherosclerosis: a scoping review - Suhaimi, Nur Farhanah Aqilah; Mamat, Suhana (Kulliyyah of Allied Health Sciences, IIUM, 2025)
Atherosclerosis is an inflammatory disease that involves the formation of plaque in large arteries. It is a leading cause of vascular death worldwide, and current therapy is not effective for all patients. Recently, mesenchymal stem cell-derived exosome particles have shown potential as treatment for this disease. Therefore, this scoping review is to provide an overview and determines the extent of research on its potential for use as treatment in atherosclerosis. For article search, five online databases were used, namely Scopus, Science Direct, Cambridge Journal, PubMed, and Cochrane Library. Keywords (atherosclerosis OR atherogenesis) AND (‘mesenchymal cell’ OR ‘stem cell’) AND (exosome OR exosomes) were used. After the screening steps, irrelevant articles were removed and the final retrieval steps provided 10 full-text articles to be reviewed. The summary of the core concepts that were used in all relevant articles showed that inflammation is the most targeted process in this disease development followed by inhibition of apoptosis and facilitation of movement of cells that contributes to the atherogenesis. In most papers, exosomes from mesenchymal stem cells were used as vehicles to transport biological components to the targeted site, in vitro or in vivo.Only one paper reported on the antiatherogenic effect of exosomes in vivo. Several issues remain to be elucidated, such as the best method to extract the exosomes, their specific component that promotes antiatherogenic effects, their interaction with the inflammatory and immune cells, the optimum level needed for intervention and their stability once injected in vivo. In conclusion, there are a lot of research gaps that should be addressed in order to use exosomes from mesenchymal cells in atherosclerosis treatment.